Prospective study of a panfungal PCR assay followed by sequencing, for the detection of fungal DNA in normally sterile specimens in a clinical setting: a complementary tool in the diagnosis of invasive fungal disease?. (26th April 2013) - Babouee, B.; Goldenberger, D.; Elzi, L.; Lardinois, D.; Sadowski‐Cron, C.; Bubendorf, L.; Savic Prince, S.; Battegay, M.; Frei, R.; Weisser, M.
Abstract: We prospectively analyzed 34 clinical biopsy samples from 23 patients with a suspected invasive fungal infection by fungal culture, histology and a panfungal PCR followed by sequencing. Results were compared to the composite diagnosis according the European Organization for Research and Treatment of Cancer (EORTC) criteria. In 34 samples, culture, histology and panfungal PCR were positive in 35%, 38% and 62%, respectively. On the sample level the panfungal PCR revealed a sensitivity of 69% and a specificity of 62.5% compared to proven IFI according postoperative EORTC criteria. On patient level, the sensitivity of the PCR approach was 100%, specificity 62.5%.